Multimodal hard X-ray imaging of a mammography phantom at a compact synchrotron light source - Schleede, Simone (International Union of Crystallography, 2012)
The Compact Light Source is a miniature synchrotron producing X-rays at the interaction point of a counter-propagating laser pulse and electron bunch through the process of inverse Compton scattering. The small transverse size of the luminous region yields a highly coherent beam with an angular divergence of a few milliradians. The intrinsic monochromaticity and coherence of the produced X-rays can be exploited in high-sensitivity differential phase-contrast imaging with a grating-based interferometer. Here, the first multimodal X-ray imaging experiments at the Compact Light Source at a clinically compatible X-ray energy of 21 keV are reported. Dose-compatible measurements of a mammography phantom clearly demonstrate an increase in contrast attainable through differential phase and dark-field imaging over conventional attenuation-based projections.